The return of the old masquerader-scurvy: a case report of pediatric limping and bone pain - Xavier Chan; Wen Wei Christopher Ho; Sudipta Roy Chowdhury (SpringerOpen, 2024)
Abstract Background Scurvy has been a rare condition in the developed world due to the increasing availability of adequate nutrition and easy access to fruits and vegetables. Scurvy is caused by severe vitamin C deficiency and has been historically associated with malnutrition in high-risk populations such as sailors. As it is an uncommon nutritional deficiency, scurvy is seldom suspected and usually under-diagnosed especially in the pediatric population. Case presentation We report a case of a pediatric patient with a history of autism spectrum disorder presenting with atypical symptoms of scurvy with gait abnormalities, diffuse rash, musculoskeletal deconditioning, and bleeding manifestations. After multiple extensive investigations and a prolonged hospitalization, a detailed dietary analysis revealed a severely restricted diet devoid of fruits and vegetables. Physical examination revealed specific signs of corkscrew hair with peri-follicular hemorrhages, hypertrophic, and bleeding gums with a concurrent low vitamin C level. Treatment with vitamin C supplementation was initiated and he was ambulant within 1 month of discharge. Conclusion This case highlights the importance of nutrition history for determining micronutrient deficiency in children with special needs. Enhanced physician education and higher index of suspicion regarding nutritional deficiencies will avoid over-investigations and delays for the institution of specific treatment.